PENINGKATAN SISTEM IMUN OLEH KOMBINASI EKSTRAK ETANOL DAUN AWAR – AWAR (Ficus septica burm. F) DAN EKSTRAK ETANOL DAUN KELOR (Moringa oleifera) SEBAGAI KO-KEMOTERAPI KANKER PADA TIKUS PUTIH BETINA GALUR SPRAGUE DAWLEY YANG DIINDUKSI DOKSORUBISIN - Rizka Angerti Anovia; Dewi Indah Sari; Annisa Hardikasari Yazin; Ulfa Ismayani; Endang Darmawan (Pharmaciana, 2015)
Use of the drug doxorubicin for cancer therapy causes decreasing of immune system reported. Leaves of Ficus septica Burm. F and leaves of Moringa oleifera as immunostimulatory agents. The purpose of this study, among others, determine the combined effects of ethanol extract of Ficus septica Burm. F leaves and ethanol extract of Moringa oleifera leaves as co-chemotherapy for in female rats Sprague Dawley strain induced doxorubicin. Eighteen Sprague Dawley rats were divided into six treatment groups, normal group was given 0.9% NaCl 10ml / kgBB, positive control group were given by doxorubicin with dose of 4.67 mg / kgBB, single-dose treatment group were each given ethanol extract of Ficus septica Burm F leaves dose of 750 mg / kgBB and ethanol extract of Moringa oleifera leaves 500 mg / kgBB, treatment groups were given by combination of ethanol extract Ficus septica Burm. F leaves and Moringa oleifera leaves with a dose of 1.25 g / kgBB and a dose of 1 , 75 g / kgBB. treatment carried out for 7 days. On days 1 and 4 of each treatment groups except the normal group induced by doxorubicin 4.67 mg / kgBB intramuscularly. Blood sampling performed on day 0 and 7 th for lymphocytes CD3+ and lymphocytes CD8+ test. The results showed that the combination of ethanol extract Ficus septica burm. F leaves and Moringa oleifera leaves dose of 1.25 g / kgBB and the dose of 1.75 g / kgBB can enhanched immune system relative small which was not statistically significantly different (p> 0.05). However, a single dose of ethanol extract Moringa oleifera leaves dose of 500 mg/kg have immunostimulatory activity as lymphocytes CD3+ and lymphocytes CD8+ were more effective than a single dose of ethanol extract of Ficus septica Burm. F leaves dose of 750 mg/kgBB.